Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1098/rstb.2018.0125
|View full text |Cite
|
Sign up to set email alerts
|

Inter-generational consequences for growing Caenorhabditis elegans in liquid

Abstract: In recent years, studies in Caenorhabditis elegans nematodes have shown that different stresses can generate multigenerational changes. Here, we show that worms that grow in liquid media, and also their plate-grown progeny, are different from worms whose ancestors were grown on plates. It has been suggested that C. elegans might encounter liquid environments in nature, although actual observations in the wild are few and far between. By contrast, in the laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 67 publications
3
12
0
Order By: Relevance
“…Several inherited multigenerational responses that last for more than two generations are dependent on RNAi pathways 16,52 . Consistent with recent reports of responses that last only one or two generations being transmitted independent of these pathways, heritable immunity to microsporidia (which lasts a single generation) is not reliant on RNAi machinery 19,37 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Several inherited multigenerational responses that last for more than two generations are dependent on RNAi pathways 16,52 . Consistent with recent reports of responses that last only one or two generations being transmitted independent of these pathways, heritable immunity to microsporidia (which lasts a single generation) is not reliant on RNAi machinery 19,37 .…”
Section: Discussionsupporting
confidence: 88%
“…To explore this, we tested whether mutants defective in small-RNA inheritance and histone modification were able to transmit immunity phenotypes to offspring. We found that the offspring of N. parisii infected mutants still became protected against infection ( Figure S7A-D) 19,37 . In addition, we found that the master immune regulator PMK-1 was not required for the induction of immunity, consistent with this pathway not being involved in immunity to N. parisii ( Figure S7C-D) 27 .…”
Section: The Parental Transcriptional Response To Infection Triggers mentioning
confidence: 91%
See 1 more Smart Citation
“…HIF-1 depletion did not increase P hsp-6 ::GFP (average FC 1.067) in our screen as when assayed on plate (Figure 3A). One possible explanation is that liquid growing conditions are energetically more demanding, metabolism is altered and the UPR mt might be differentially regulated [59]. We reasoned that transcription factors that genetically interact with sgk-1 should further reduce worm size.…”
Section: Resultsmentioning
confidence: 99%
“…First, lifespan of worms grown in monoxenic liquid culture may be different from those grown on solid medium [179]. Worms grown in liquid culture are longer [245] and have a higher incidence of internal hatching [246] compared to NGM agar. Liquid culture also induces changes in gene expression [247,248].…”
Section: Liquid Culture-based Lifespan Assaysmentioning
confidence: 99%